Regulations of the financial market in Poland. Equilibrium vs. inversion - Dziawgo, Leszek; Dziawgo, Danuta (Regulacje rynku finansowego w Polsce. Equilibrium vs. inwersja, 2018)
The subject of this study is the legal regulations concerning the banking and stock market sector. The research objective is to identify the issue of the adequacy of legal regulations on the modern financial market. The object of the research is the banking institutions and companies listed on the stock exchange. The following research methods were used, i.e. the analysis of the literature, analysis of legal acts, observations, descriptive, comparative and case study analysis. It was found that there has been an increase in the level of detail and restrictiveness of legal regulations in recent years, both in relation to the banking sector and to the stock market. In addition, the legislative revolution not only continues, but is also gaining momentum. Thus we could formulate a conclusion about the inversion of the modern financial market. The financial market was to facilitate business operations through access to capital. Currently, excessive regulations indicate the growing legal barriers to entering the financial market and conducting business activity in it
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 4, s. 9-24
Keywords: banking; public companies; law regulations; financial market